Analisis Permenkop UMKM No 3 Tahun 2021 terhadap Program Pemberdayaan UMKM pada Koperasi Masjid di Kopsyahmas Mungsolkanas Bandung - Tri Ambarwati; Zaini Abdul Malik; Arif Rijal Anshori (Bandung Conference Series: Sharia Economic Law, 2024)
Abstract. Empowerment is a development process that makes people take the initiative in social activities to improve their situation and conditions. MSMEs are business activities carried out by individuals or groups but with small businesses. Minister of Cooperatives and UMKM Regulation No. 3 of 2021 which explains the convenience and protection of Cooperatives and MSMEs. One of the Kopsyahmas Mosque Cooperatives has approximately thirty MSME business actors who provide financing and carry out empowerment, so the author wants to know about the empowerment practices carried out by the Mungsolkanas Cooperative and the analysis of Permenkop MSMEs No. 3 of 2021 on the empowerment of MSMEs in the Bandung Kopsyahmas Mosque Cooperative. The aim of this research is to analyze Permenkop UMKM No. 3 of 2021 on the empowerment of MSMEs in the Bandung Kopsyahmas Mosque Cooperative. This research uses qualitative methods with a normative juridical approach and the type of research is field research. The data collection methods used were interviews, literature study, observation and documentation. Research results The empowerment practice carried out is very easy both in terms of the terms and process and the contract used is explained in advance and mutually agreed upon by both parties. The analysis of Permenkop UMKM No. 3 of 2021 on the empowerment of MSMEs in the Bandung Kopsyahmas Mosque Cooperative is less than optimal because article 12 in Permenkop UMKM No. 3 of 2021 is not implemented comprehensively by the Kopsyahmas Mosque Cooperative. Abstrak. Pemberdayaan merupakan suatu proses pembangunan yang menjadikan masyarakat mempunyai inisiatif dalam kegiatan sosial untuk memperbaiki situasi dan kondisinya. UMKM merupakan kegiatan usaha yang dilakukan oleh perseorangan atau kelompok namun dengan usaha kecil-kecilan. Peraturan Menteri Koperasi dan UMKM Nomor 3 Tahun 2021 yang menjelaskan tentang kemudahan dan perlindungan Koperasi dan UMKM. Salah satu Koperasi Masjid Kopsyahmas mempunyai kurang lebih tiga puluh pelaku usaha UMKM yang memberikan pembiayaan dan melakukan pemberdayaan, sehingga penulis ingin mengetahui praktik pemberdayaan yang dilakukan Koperasi Mungsolkanas dan analisis Permenkop UMKM No 3 Tahun 2021 tentang pemberdayaan UMKM di Koperasi Masjid Kopsyahmas Bandung.Tujuan penelitian ini adalah menganalisis Permenkop UMKM No. 3 Tahun 2021 tentang Pemberdayaan UMKM di Koperasi Masjid Kopsyahmas Bandung. Penelitian ini menggunakan metode kualitatif dengan pendekatan yuridis normatif dan jenis penelitiannya adalah penelitian lapangan. Metode pengumpulan data yang digunakan adalah wawancara, studi literatur, observasi dan dokumentasi. Hasil Penelitian Praktek pemberdayaan yang dilakukan sangat mudah baik dari segi syarat dan prosesnya serta kontrak yang digunakan dijelaskan terlebih dahulu dan disepakati bersama oleh kedua belah pihak. Analisis terhadap Permenkop UMKM No.3 Tahun 2021 tentang Pemberdayaan UMKM pada Koperasi Masjid Kopsyahmas Bandung kurang optimal karena pasal 12 pada Permenkop UMKM No.3 Tahun 2021 tidak diterapkan secara komprehensif oleh Koperasi Masjid Kopsyahmas.